Effects of Oral Commensal Streptococci on Porphyromonas gingivalis Invasion into Oral Epithelial Cells - Alyssa N. Hanel; Hannah M. Herzog; Michelle G. James; Giancarlo A. Cuadra (MDPI AG, 2020)
The objective of this study was to determine if the interaction between common oral commensal bacteria and oral epithelial cells would provide protective effects against the invasion of periodontopathogen Porphyromonas gingivalis. Oral epithelial OKF6/Tert cells were used in co-cultures with Streptococcus gordonii, Streptococcus oralis, Streptococcus mitis, and Streptococcus intermedius. The viability of OKF6/Tert cells following a bacterial challenge was evaluated by trypan blue exclusion. The adherence of commensal species was determined by CFU counts. P. gingivalis invasion in OKF6/Tert cells was assessed before and after exposure to commensal species according to CFU counts. Viability assays show that only S. gordonii and S. intermedius display low toxicity toward OKF6/Tert cells. Both commensals adhere to OKF6/Tert cells at an average ratio of 1 CFU to 10 cells. P. gingivalis invasion into host cells is significantly reduced by 25% or 60% after exposure to S. gordonii or S. intermedius, respectively. The results suggest that these commensal species bind to host cells and diminish P. gingivalis invasion. This is important in the context of periodontal disease since P. gingivalis primarily acts on the host by invading it. Therefore, efforts to decrease invasion will eventually lead to future therapies harnessing the mechanisms employed by oral commensal bacteria.